UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU DENGAN MENGGUNAKAN METODE DISKUSI DI SMAN 3 LANGGAM KABUPATEN PELALAWAN PROVINSI RIAU - JURNIATI JURNIATI (JURNAL ILMIAH KOHESI, 2022)
The research objective is the principal's efforts to increase teacher motivation using the discussion method at SMAN 3 Langgam, Pelalawan Regency. The school action research research method (PTS). Based on the results of the study it can be concluded that the efforts of the principal in increasing teacher motivation using the discussion method obtained the results of the findings of the first cycle of the second meeting obtained an average success in increasing teacher motivation in learning only reached 69%, because the teacher was not successful in cycle I, continued in cycle II, in II using the group discussion method, teacher motivation increased to 82.5%. Because the findings were in accordance with what was expected, the research was stopped in cycle II, there was an increase in teacher motivation by 13.5%.